The Impact of Absent Coworkers on Productivity in Teams - Sam Hoey; Thomas Peeters; Jan C. van Ours (Institute of Labor Economics (IZA), 2022)
We study how workers in production teams are affected by the temporary absence and replacement of a coworker. When a substitute coworker is absent, the remaining coworkers produce less output per working time. They compensate for this by increasing their working time at the expense of the (less able) replacement worker, such that the output loss per remaining worker is not significant. When a complementary coworker is absent, we see a similar loss in output per minute worked, but this directly leads to a loss of output produced, because remaining workers do not take over the absent worker's tasks.
Keywords: M50; M54; J24; 330; absenteeism; worker productivity; team production; ice hockey